Preparation method and application of positive electrode sheet
Patent Information
- Application Number
- CN202311803196.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-12-26
AI Technical Summary
但目前仅通过增加极片涂覆面密度制备的高面密正极极片存在以下问题:(1)面密度的提高导致极片厚度增加,需延长烘干过程的时间,而浆料中粘结剂因分子量小、质量轻、体积小易穿梭,加热后更容易上浮聚集在极片表面,缺少粘结剂的底部浆料烘干后和箔材的粘接效果变差,降低了极片的剥离力,易引起电芯内部短路和析锂:(2)面密度的提高导致极片厚度增加,极片的电阻增大,且使得充放电时候锂离子传输路径更远,降低了离子扩散性能力,加剧了离子转移阻抗和扩散阻抗,导致电芯内阻增大
[0035] 1. This invention treats the surface of the current collector by corona discharge and drying, which fully removes residual oil and repairs surface tension. At the same time, the generation of free radicals on the surface introduces a large number of polar groups, thereby obtaining a current collector with a high coefficient value. This is beneficial for wetting the slurry on its surface and greatly increases the possibility of covalent bonding during the bonding process, thus improving the bonding effect between the current collector and the active layer.
Smart Images

Figure CN117766686B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a method for preparing and applying a positive electrode sheet. Background Technology
[0002] Lithium-ion batteries possess advantages such as long cycle life, high energy density, and low cost, and have been increasingly widely used in various electronic products, power tools, electric vehicles, and energy storage devices in recent years. With the large-scale application of lithium-ion batteries in electric vehicles, the requirements for battery capacity and rate performance are becoming increasingly stringent.
[0003] As an important component of the lithium-ion battery system, the positive electrode plays a crucial role in storing and releasing lithium ions during the charging and discharging process of the lithium battery. It not only determines the energy density of the battery, but its resistance also directly affects the rate performance and cycle life of the cell. To improve the energy density of the battery, a common method is to increase the coating density of the electrode to prepare a high-density positive electrode with high capacity. However, the high-density positive electrode prepared by increasing the coating density of the electrode has the following problems: (1) The increase in the coating density leads to an increase in the thickness of the electrode, which requires a longer drying time. The binder in the slurry is easy to shuttle due to its small molecular weight, light weight, and small volume. After heating, it is easier to float and gather on the surface of the electrode. The adhesion effect between the bottom slurry and the foil is worse after drying due to the lack of binder, which reduces the peeling force of the electrode and is prone to short circuit and lithium plating inside the cell. (2) The increase in the coating density leads to an increase in the thickness of the electrode, which increases the resistance of the electrode and makes the lithium ion transport path longer during charging and discharging. This reduces the ion diffusion capacity, aggravates the ion transfer impedance and diffusion impedance, and leads to an increase in the internal resistance of the cell. While increasing the proportion of binder in the positive electrode active slurry can overcome the problem of low electrode peeling force, it will exacerbate the increase in membrane resistance. If the proportion of conductive agent in the positive electrode active slurry is increased at the same time, the membrane resistance will be reduced, but the reduced proportion of positive electrode active material will lead to a decrease in battery capacity.
[0004] Therefore, how to effectively balance the peeling force and film resistance of high areal density positive electrode sheets while meeting capacity requirements is a challenging problem that the industry urgently needs to solve. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a positive electrode sheet and its application. By simultaneously preparing a double coating with the same or different component ratios on a current collector with a high coefficient value, and then drying and rolling the coating, a high areal density positive electrode sheet with high peel strength and low film resistance is obtained.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0007] The first aspect of this invention provides a method for preparing a positive electrode sheet, comprising the following steps:
[0008] (1) The current collector is subjected to corona treatment and drying treatment in sequence to obtain the pretreated current collector;
[0009] (2) Prepare a first positive electrode active slurry and a second positive electrode active slurry by mixing positive electrode active material, conductive agent, binder and solvent according to a preset ratio, and coat them on the surface of the pretreated current collector to form a first coating and a second coating; the first coating is obtained by coating the first positive electrode active slurry and is in contact with the current collector; the second coating is obtained by coating the second positive electrode active coating and is in contact with the side of the first coating away from the current collector;
[0010] (3) After drying and rolling, the positive electrode sheet is obtained;
[0011] In step (2), the solid content p1 in the first positive electrode active slurry and the solid content p2 in the second positive electrode active slurry are both 70% to 80%; and the binder ratio n1 in the first positive electrode active slurry and the binder ratio n2 in the second positive electrode active slurry satisfy: 2.0% > n1 ≥ n2 ≥ 0.7%.
[0012] The binder percentage n1 in the first positive electrode active slurry is the ratio of the mass of the binder in the first positive electrode active slurry to the total mass of the non-solvent substances (positive electrode active material + conductive agent + binder); the binder percentage n2 in the second positive electrode active slurry is the ratio of the mass of the binder in the first positive electrode active slurry to the total mass of the non-solvent substances (positive electrode active material + conductive agent + binder).
[0013] Further, in step (1), a method of corona treatment and drying is adopted to improve the dyne value of the current collector surface. In the corona treatment step, the corona power is 1-6kW, the corona distance is 2-4mm, and the corona time is 0.01-120s. In the drying treatment step, the drying temperature is 40-60℃ and the belt speed is 15-50m / min.
[0014] Further, in step (1), the dyne value of the pretreated current collector surface is 30-65, more preferably 50-65.
[0015] Further, in step (2), the mass ratio of positive active material, conductive agent and binder in the first positive active slurry and the second positive active slurry is 95-98:0.5-2:0.2-3; the viscosity of the first positive active slurry and the second positive active slurry is 5000-15000 mpa.s, and the fineness is ≤40 μm.
[0016] Further, in step (2), a double-layer coating die is used to simultaneously coat the surface of the current collector to form a first coating and a second coating. The double-layer coating die includes upper and lower liquid outlets, which are respectively connected to a slurry conveying system. The slurry conveying system consists of a feeding cart, a screw pump, and a conveying pipe. The first positive electrode active slurry and the second positive electrode active slurry are extruded through the lower and upper liquid outlets of the double-layer coating die and coated onto the pretreated surface of the current collector, simultaneously forming the first coating and the second coating.
[0017] Further, in step (2), the coating process involves: a coating speed of 5-30 m / min, and a single-sided coating density of 0.4-0.6 (g / 1540.25 mm²) for the current collector; and a single-layer coating surface density of 0.2-0.3 (g / 1540.25 mm²) for both the first and second coatings. The single-layer coating surface density refers to the surface density of each coating after drying.
[0018] Further, in step (2), the ratio of the surface density of the first coating layer to the surface density of the second coating layer is m1 / m2, which is 0.95. <m1 / m2<1.05。
[0019] Furthermore, p1 and p2 are more preferably 72%-78%, such as 73%, 74%, 75%, 76%, 77%, etc.
[0020] Further, n1 is preferably 1.0%-1.6%, n2 is preferably 0.7%-1.3%; n2 is more preferably 1.0%-1.3%, and / or n1-n2≥0.3%.
[0021] Furthermore, in step (3), the drying temperature is 50-150℃.
[0022] Furthermore, in step (3), after the rolling process, the compaction density of the positive electrode sheet is 2.0-4.5 g / cm³. 3 .
[0023] A second aspect of the present invention provides a positive electrode sheet prepared by the preparation method of the first aspect, the positive electrode sheet comprising a current collector, a first active layer disposed on at least one side of the current collector, and a second active layer disposed on the first active layer.
[0024] Furthermore, the material of the current collector includes, but is not limited to, aluminum foil with a thickness of 5-20 μm; the thickness of the positive electrode sheet is 0.05-2 mm.
[0025] Furthermore, the preparation of the positive electrode sheet shall simultaneously satisfy the following conditions:
[0026] (1) The dyne value of the pretreated current collector surface is 50-65;
[0027] (2) p1 and p2 are both 72%-78%;
[0028] (3) n1 is 1.0%-1.6%, and n2 is 0.7%-1.3%;
[0029] (4) The conductive agent in the first positive electrode active slurry and the second positive electrode active slurry is composed of conductive carbon black and carbon nanotubes. The mass percentage of conductive carbon black in the first active layer and the second active layer is 0.9%-1.1%, and the mass percentage of carbon nanotubes in the first active layer and the second active layer is 0.7%-0.9%.
[0030] (5) The surface density of both the first and second coatings is 0.2-0.3 (g / 1540.25mm2), and the ratio of the surface density of the first coating to that of the second coating is m1 / m2, 0.95. <m1 / m2<1.05;
[0031] The peel strength of the positive electrode sheet is Y1 = a × ln(x1) + ab, where 10 ≤ a ≤ 13, 7 ≤ b ≤ 10, and x1 is the areal density of the binder in the first active layer, x1 = m1 × n1, with the unit being g / 1540.25 mm2;
[0032] The film resistance of the positive electrode is Y2 = c × e d×c×(x1+x2) Where 0.20≤c≤0.32, 1200≤d≤1800, and x2 is the areal density of the adhesive in the second active layer, x2=m2×n2, with the unit being g / 1540.25mm2.
[0033] A third aspect of the present invention provides a lithium-ion battery comprising the positive electrode sheet described in the second aspect.
[0034] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0035] 1. This invention treats the surface of the current collector by corona discharge and drying, which fully removes residual oil and repairs surface tension. At the same time, the generation of free radicals on the surface introduces a large number of polar groups, thereby obtaining a current collector with a high coefficient value. This is beneficial for wetting the slurry on its surface and greatly increases the possibility of covalent bonding during the bonding process, thus improving the bonding effect between the current collector and the active layer.
[0036] 2. This invention achieves high areal density coating by adjusting the slurry composition ratio and simultaneously forming a first and second coating on the current collector surface (e.g., using a double-layer extrusion die to simultaneously extrude the first and second positive electrode active slurries to form the first and second coatings). The above preparation process is simple to operate and has controllable quality. Coatings with the same or different slurries can be prepared in a single coating step. The simultaneous drying of different coatings can effectively improve the bonding force between them. More importantly, this invention can effectively alleviate the problem of low peel force between the active layer and the current collector due to the upward movement of the binder during the drying process, and the problem of excessively high membrane resistance due to excessive binder content, by adjusting the solid content of the first and second positive electrode active slurries and the proportion of binder.
[0037] 3. The positive electrode sheet prepared by the above-mentioned preparation process can not only effectively improve the problems of bulging edges, false edges, cracking and inconsistent surface density that are easy to occur in the current preparation process of high surface density positive electrode sheets, but also meet the requirements of high peeling force and low film resistance while ensuring that the high surface density positive electrode sheet meets the capacity requirements. This allows the lithium-ion battery containing the high surface density positive electrode sheet to have the advantages of high capacity, high rate performance and long cycle life. Attached Figure Description
[0038] Figure 1 This is a schematic diagram of the preparation of the positive electrode active layer, where 1 is the support roller, 2 is the double-layer extrusion die, 3 is the current collector, 4 is the first positive electrode active slurry, and 5 is the second positive electrode active slurry. Detailed Implementation
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items. "Comprising" or "containing" as used herein means that it may include or contain other components in addition to the stated components. "Comprising" or "containing" as used herein may also be replaced with the closed form "is" or "consisting of".
[0040] As described in the background section, the current preparation of high areal density positive electrode sheets suffers from low peel strength and high film resistance. While increasing the proportion of binder in the positive electrode active slurry can overcome the low peel strength problem, it exacerbates the increase in film resistance. Conversely, increasing the proportion of conductive agent in the positive electrode active slurry reduces film resistance, but the reduced proportion of positive electrode active material leads to a decrease in battery capacity. Therefore, effectively balancing the peel strength and film resistance of the positive electrode film while ensuring that the high areal density positive electrode sheet meets capacity requirements is a pressing issue that the industry needs to address.
[0041] To address the aforementioned technical problems, embodiments of the present invention provide a method for preparing a positive electrode sheet, comprising the following steps:
[0042] (1) The current collector is subjected to corona treatment and drying treatment in sequence to obtain the pretreated current collector;
[0043] (2) Prepare a first positive electrode active slurry and a second positive electrode active slurry by mixing positive electrode active material, conductive agent, binder and solvent according to a preset ratio, and coat them on the surface of the pretreated current collector to form a first coating and a second coating; the first coating is obtained by coating the first positive electrode active slurry and is in contact with the current collector; the second coating is obtained by coating the second positive electrode active coating and is in contact with the side of the first coating away from the current collector;
[0044] (3) After drying and rolling, the positive electrode sheet is obtained;
[0045] In step (2), the solid content p1 in the first positive electrode active slurry and the solid content p2 in the second positive electrode active slurry are both 70% to 80%; and the binder ratio n1 in the first positive electrode active slurry and the binder ratio n2 in the second positive electrode active slurry satisfy: 2.0% > n1 ≥ n2 ≥ 0.7%.
[0046] Wherein, the proportion of binder n1 in the first positive electrode active slurry is the ratio of the mass of binder in the first positive electrode active slurry to the total mass of non-solvent substances (positive electrode active material + conductive agent + binder); the proportion of binder n2 in the second positive electrode active slurry is the ratio of the mass of binder in the first positive electrode active slurry to the total mass of non-solvent substances (positive electrode active material + conductive agent + binder).
[0047] This invention improves the peel force between the current collector and the active layer by addressing both the current collector end and the active layer end. The improved treatment at the current collector end involves a combined corona treatment and drying process to remove residual oil and restore surface tension. Simultaneously, free radicals are generated on the current collector surface, introducing a large number of polar groups. This results in a current collector with a high coefficient of thermality, which facilitates slurry wetting and significantly increases the likelihood of covalent bonding during the adhesion process, thereby enhancing the adhesion between the current collector and the active layer.
[0048] Furthermore, this invention achieves the preparation of a high areal density coating by adjusting the slurry composition ratio and simultaneously extruding the upper and lower slurries using a double-layer extrusion die to form a first and second coating on the current collector surface. This preparation process is simple to operate and offers more controllable quality. Coatings with the same or different slurries can be prepared in a single coating step, and simultaneous drying of different coatings can effectively improve the bonding strength between them. In addition, in the above-mentioned preparation process of the high areal density positive electrode sheet, the problems of low peel strength and excessively high membrane resistance in current high areal density products can be improved by adjusting the solid content of the first and second positive electrode active slurries and the proportion of binder. For example, by increasing the proportion of binder in the first positive electrode active slurry and decreasing the proportion of binder in the second positive electrode active slurry, the first active layer can still adhere firmly to the current collector after drying, thereby improving the peel strength between the active layer and the current collector, while avoiding excessively high total binder content in the active layer that would affect the membrane resistance, thus obtaining a high areal density positive electrode sheet with high peel strength and low membrane resistance.
[0049] In some preferred embodiments, in step (1), during the corona treatment step: the corona power is 1-6kW, the corona distance is 2-4mm, and the corona time is 0.01-120s, where the corona distance is the distance between the discharge electrode of the corona processor and the current collector; during the drying step: the drying process is carried out in an oven at a temperature of 40-60℃ and a conveyor belt speed of 15-50m / min. When the current collector pretreatment and coating can be performed simultaneously, the conveyor belt speed is consistent with the coating speed.
[0050] In some preferred embodiments, the dyne value of the pretreated current collector surface in step (1) is preferably 30-65, such as 30, 35, 40, 45, 50, 55, 60, 65, etc., including but not limited to the values listed above; the dyne value of the pretreated current collector surface is more preferably 50-65.
[0051] In some preferred embodiments, in step (2), the mass ratio of positive electrode active material, conductive agent and binder in the first positive electrode active slurry and the second positive electrode active slurry is preferably 95-98:0.5-2:0.2-3; the viscosity of the first positive electrode active slurry and the second positive electrode active slurry is preferably 5000-15000 mpa.s and the fineness is ≤40 μm.
[0052] In some preferred embodiments, in step (2), the first positive electrode active slurry and the second positive electrode active slurry are simultaneously coated on the surface of the current collector using a double-layer coating die to form a first coating and a second coating; the double-layer coating die includes upper and lower liquid outlets, each connected to a slurry conveying system, which consists of a feeding cart, a screw pump and a conveying pipe.
[0053] In some preferred embodiments, p1 and p2 are both 72%-78%, such as 72%, 72.5%, 73%, 74%, 74.5%, 75%, 75.3%, 76%, 76.2%, 76.5%, 77%, 78%, etc., including but not limited to the values listed above; n1 is 1.0%-1.6%, such as 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, etc.; n2 is 0.7%-1.3%, such as 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, etc., including but not limited to the mass percentages listed above, wherein n2 is more preferably 1.0%-1.3%, and / or n1-n2≥0.3%, for example, n1 is 1.3% and n2 is 1.0%.
[0054] In some preferred embodiments, during the coating process: the coating speed is 5-30 m / min, and the single-sided coating density of the current collector is 0.4-0.6 (g / 1540.25 mm²); wherein the single-layer coating surface density of both the first and second coatings is 0.2-0.3 (g / 1540.25 mm²); more preferably, the ratio of the single-layer coating surface density of the first coating to the single-layer coating surface density of the second coating is m1 / m2, 0.95. <m1 / m2<1.05。
[0055] The surface density of the single-layer coating mentioned above refers to the surface density of each coating after drying. Before coating, the surface density of each individual coating is calibrated. Once the surface density meets the requirements, the first and second coatings are prepared simultaneously.
[0056] In some preferred embodiments, the drying temperature in step (3) is 50-150°C; more preferably, the coating and drying processes are carried out simultaneously.
[0057] In some preferred embodiments, in step (3), after the rolling process, the compaction density of the positive electrode sheet is 2.0-4.5 g / cm³. 3 For example, 2.0 g / cm³ 3 2.1g / cm 3 2.3g / cm 3 2.5g / cm 3 2.8g / cm 3 3.0g / cm 3 3.2g / cm 3 3.5g / cm 3 3.7g / cm 3 4.0g / cm 3 4.1g / cm 3 4.2g / cm 3 4.4 g / cm 3 4.5g / cm 3 And so on, including but not limited to the values listed above.
[0058] The positive electrode sheet prepared by the above-mentioned preparation process can not only effectively improve the problems of bulging edges, false edges, cracking and inconsistent surface density that are easy to occur in the current preparation process of high surface density positive electrode sheets, but also meet the requirements of high peeling force and low film resistance while ensuring that the high surface density positive electrode sheet meets the capacity requirements.
[0059] An embodiment of the present invention also provides a positive electrode sheet prepared by the above-described preparation method. The positive electrode sheet includes a current collector, a first active layer disposed on at least one side of the current collector, and a second active layer disposed on the first active layer.
[0060] In some preferred embodiments, the current collector is made of materials including but not limited to aluminum foil, with a preferred thickness of 5-20 μm; the positive electrode sheet has a preferred thickness of 0.05-2 mm.
[0061] In some preferred embodiments, the positive electrode sheet is prepared when the following conditions are met simultaneously:
[0062] (1) The dyne value of the pretreated current collector surface is 50-65;
[0063] (2) p1 and p2 are both 72%-78%;
[0064] (3) n1 is 1.0%-1.6%, and n2 is 0.7%-1.3%;
[0065] (4) The conductive agent in the first positive electrode active slurry and the second positive electrode active slurry is composed of conductive carbon black and carbon nanotubes. The mass percentage of conductive carbon black in the first active layer and the second active layer is 0.9%-1.1%, and the mass percentage of carbon nanotubes in the first active layer and the second active layer is 0.7%-0.9%.
[0066] (5) The surface density of both the first and second coatings is 0.2-0.3 (g / 1540.25mm2), and the ratio of the surface density of the first coating to that of the second coating is m1 / m2, 0.95. <m1 / m2<1.05;
[0067] The peel strength of the positive electrode sheet is Y1 = a × ln(x1) + ab, where 10 ≤ a ≤ 13, 7 ≤ b ≤ 10, and x1 is the areal density of the binder in the first active layer, x1 = m1 × n1, with the unit being g / 1540.25 mm2;
[0068] The film resistance of the positive electrode is Y2 = c × e d×c×(x1+x2) Where 0.20≤c≤0.32, 1200≤d≤1800, and x2 is the areal density of the adhesive in the second active layer, x2=m2×n2, with the unit being g / 1540.25mm2.
[0069] Under high areal density conditions, the peel strength Y1 is mainly affected by the binder content in the first active layer. As the binder ratio in the first active layer increases, there is a diminishing marginal effect in the increase of peel strength (i.e., the binder dosage reaches saturation, and further increases will affect the proportion of active material). Under the above conditions, the peel strength Y1 has a logarithmic relationship with the binder content in the lower slurry. Under the same conditions, the membrane resistance Y2 is affected by the binder content in the overall active layer. Within a certain range, as the binder ratio increases, the membrane resistance Y2 has a positively correlated logarithmic relationship with the binder content in the overall active layer. This invention, through testing the membrane resistance and peel strength of the positive electrode sheet prepared by the above preparation method, fits the relationship between peel strength and the binder dosage in the first active layer, and the relationship between membrane resistance and the total binder dosage in the active layer, which can predict the electrode sheet condition in advance at the design stage.
[0070] The aforementioned positive electrode sheet can be used to prepare lithium-ion batteries, enabling lithium-ion batteries containing this high areal density positive electrode sheet to have the advantages of high capacity, high rate performance, and long cycle life.
[0071] The present invention will be further described below with reference to specific embodiments, so that those skilled in the art can better understand and implement the present invention, but the embodiments are not intended to limit the present invention.
[0072] Example 1
[0073] This embodiment relates to the preparation of a positive electrode sheet, and the specific operation is as follows:
[0074] (1) The current collector with a thickness of 13μm was subjected to corona treatment and drying treatment in sequence. The surface dyne value of the current collector after pretreatment was 60. The power of the online corona processor was 6kW, the distance between the online corona processor and the copper foil was 3mm, and the corona treatment time was 8s. The temperature of the oven used for drying treatment was 50℃, and the conveyor belt speed was 30m / min.
[0075] (2) The positive electrode active material, conductive agent, binder, and solvent were added to a planetary mixer according to a preset ratio. The planetary mixer's paddle rotation speed was 25 rpm, the dispersion disc rotation speed was 1500 r / min, and the mixing time was 240 min, resulting in a second positive electrode active slurry with a viscosity of 10550 mPa·s and a solid content of 75% and a first positive electrode active slurry with a viscosity of 12387 mPa·s and a solid content of 75%. The mass ratio of the positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes (CNTs), and binder (PVDF) in the first positive electrode active slurry was 97.2:1.0:0.8:1.0; the mass ratio of the positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes (CNTs), and binder (PVDF) in the second positive electrode active slurry was also 97.2:1.0:0.8:1.0.
[0076] The prepared first positive electrode active slurry and second positive electrode active slurry are extruded using a double-layer extrusion die (such as...). Figure 1 As shown, a first coating and a second coating are formed on the pretreated surface of the current collector. The first coating adheres to the current collector, and the second coating adheres to the side of the first coating away from the current collector. The surface density of both the first and second coatings is 0.2 g / 1540.25 mm². 2 ).
[0077] (3) After drying and roller pressing, the compacted density is 3.0 g / cm³. 3 The positive electrode plate A1.
[0078] Example 2
[0079] This embodiment relates to the preparation of a positive electrode sheet A2. The difference from Embodiment 1 lies only in the formulation of the first and second positive electrode active slurries, as follows: In the first positive electrode active slurry prepared in this embodiment, the mass ratio of positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes, and binder (PVDF) is 96.9:1.0:0.8:1.3; in the second positive electrode active slurry, the mass ratio of positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes, and binder (PVDF) is 97.2:1.0:0.8:1.0.
[0080] Example 3
[0081] This embodiment relates to the preparation of a positive electrode sheet A3. The difference from Example 1 lies only in the formulation of the first and second positive electrode active slurries, as follows: In the first positive electrode active slurry prepared in this embodiment, the mass ratio of positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes, and binder (PVDF) is 96.9:1.0:0.8:1.3; in the second positive electrode active slurry, the mass ratio of positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes, and binder (PVDF) is 96.9:1.0:0.8:1.3.
[0082] Example 4
[0083] This embodiment relates to the preparation of a positive electrode sheet A4. The difference from Embodiment 1 lies only in the formulation of the first and second positive electrode active slurries, as follows: In the first positive electrode active slurry prepared in this embodiment, the mass ratio of positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes, and binder (PVDF) is 96.6:1.0:0.8:1.6; in the second positive electrode active slurry, the mass ratio of positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes, and binder (PVDF) is 96.9:1.0:0.8:1.3.
[0084] Example 5
[0085] This embodiment relates to the preparation of a positive electrode sheet A5. The difference from Embodiment 1 lies only in the formulation of the first and second positive electrode active slurries, as follows: In the first positive electrode active slurry prepared in this embodiment, the mass ratio of positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes, and binder (PVDF) is 96.6:1.0:0.8:0.8; in the second positive electrode active slurry, the mass ratio of positive electrode active material (NCM811) to conductive carbon black SP, carbon nanotubes, and binder (PVDF) is 96.9:1.0:0.8:0.7.
[0086] Comparative Examples 1-7
[0087] Comparative Examples 1-7 involve the preparation of positive electrode sheets A6-A12. The difference from Example 1 lies in the solid content and / or formulation of the positive electrode active slurry, as shown in Table 1 below:
[0088] Table 1
[0089]
[0090] The film resistance and peel strength of the positive electrode sheets prepared in the above embodiments and comparative examples were tested. The test process is as follows:
[0091] Membrane resistance test: Cut the dried membrane into 3×5cm samples and set aside; turn on the membrane resistance tester and perform three empty tests first. The computer will obtain the average empty resistance value R1, which is usually <0.05 milliohms; place the sample to be tested on the contact platform of the tester and perform three tests. The computer will obtain the average resistance value of the sample as R2; the actual resistance of the membrane is R = R2 - R1.
[0092] Peel strength test: The compaction density was 3 g / cm³. 3 The positive electrode sheet was cut into samples with a width of 25mm and a length of 30cm for later use. Using a tensile testing instrument, the 180° testing method was adopted. The electrode sample was attached to double-sided tape, and the other side of the double-sided tape was attached to a steel plate. One end of the tensile testing instrument was fixed to the electrode sheet, and the other end was fixed to the steel plate. The software was called up, and the computer plotted the tensile curve. The tensile data of the stable section was selected, and the average value X (N) was calculated. The peel strength Y (N / m) = X / (25 / 1000).
[0093] The test results are shown in Table 2 below:
[0094] Table 2
[0095]
[0096] As shown in Tables 1 and 2, the positive electrode sheets A1 to A5 prepared from the first and second positive electrode active slurries with suitable solid content (~75%) and binder content (2.0% > n1 ≥ n2 ≥ 0.7%) exhibit lower film resistance and higher peel strength. Specifically, the overall performance of the electrode sheet is superior when the binder solid content in the first positive electrode active slurry is 1.0-1.6% or 1.0-1.3%.
[0097] Comparing the positive electrode sheets A1 to A6, it can be seen that when the binder ratio in the first positive electrode active slurry is low (e.g., n1 < 0.7%, or 0.5% in A6), the membrane resistance is low, but the peel strength is substandard. If the binder ratio in the first positive electrode active slurry is increased to 2.0%, for example, in positive electrode sheets A7 and A8, the peel strength increases significantly, but the membrane resistance also increases substantially. From A2, A3, and A7 and A8, it can be seen that when other conditions remain unchanged, adjusting only the binder ratio in the second positive electrode active slurry does not significantly change the peel strength of the electrode, but the membrane resistance increases significantly. Therefore, within a certain range, the binder content in the first positive electrode active slurry directly affects the peel strength of the electrode, while increasing the binder content in the second positive electrode active slurry has little effect on the peel strength, but will cause a rapid increase in membrane resistance.
[0098] A comparison of positive electrode plates A9–A11 with A1 shows that reducing the solid content of both the first and second positive electrode active slurries affects the membrane resistance and peel strength. Specifically, the membrane resistance decreases with decreasing binder content, while the peel strength of the electrode also decreases significantly. Furthermore, low solid content leads to reduced capacity, failing to meet the requirements for high energy density. Conversely, simultaneously increasing both the binder ratio and solid content in the first positive electrode active slurry (e.g., positive electrode plates A12 vs A4) results in a rapid increase in both peel strength and membrane resistance.
[0099] Furthermore, this invention achieves this by simply altering the surface density of the single-layer coating during the preparation of the positive electrode sheets A1 to A8, from 0.2 g / 1540.25 mm. 2 Increased to 0.3g / 1540.25mm 2 Positive electrode sheets B1 to B8 were prepared, and their film resistance and peel strength were tested. The test results are shown in Table 3 below.
[0100] Table 3
[0101]
[0102]
[0103] As shown in Table 3, compared to positive electrode sheets A1-A8, positive electrode sheets B1-B8 prepared by increasing the single-layer coating density of the first and second coatings only exhibit similar trends in film resistance and peel strength as A1-A8. Furthermore, positive electrode sheets A1-A4 and B1-B4 prepared by the method described in this invention, meeting specific preparation conditions, all show peel strength and film resistance values falling within the formulas Y1=a×ln(x1)+ab and Y2=c×e. d×c×(x1+x2) Within the calculation range.
[0104] In summary, when the solid content of the first and second positive electrode active slurries is around 75%, and the binder ratio n1 in the first positive electrode active slurry and the binder ratio n2 in the second positive electrode active slurry satisfy the following condition: 2.0% > n1 ≥ n2 ≥ 0.7%, the high areal density positive electrode sheet prepared by the preparation method described in this invention has lower film resistance and higher peel strength.
[0105] The embodiments described above are merely preferred examples to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.
Claims
1. A method for preparing a positive electrode sheet, characterized in that, Includes the following steps: (1) The current collector is subjected to corona treatment and drying treatment in sequence to obtain the pretreated current collector; (2) Prepare a first positive electrode active slurry and a second positive electrode active slurry by mixing positive electrode active material, conductive agent, binder and solvent according to a preset ratio, and apply them simultaneously to the surface of the pretreated current collector to form a first coating and a second coating; the first coating is obtained by coating the first positive electrode active slurry and is in contact with the current collector; the second coating is obtained by coating the second positive electrode active coating and is in contact with the side of the first coating away from the current collector; (3) The first coating and the second coating are dried and rolled to form a first active layer and a second active layer, thereby obtaining the positive electrode sheet; The preparation of the positive electrode sheet simultaneously satisfies the following conditions: (1) The dyne value of the pretreated current collector surface is 50-65; (2) The solid content p1 in the first positive electrode active slurry and the solid content p2 in the second positive electrode active slurry are both 72%-78%; (3) The proportion of binder n1 in the first positive electrode active slurry and the proportion of binder n2 in the second positive electrode active slurry satisfy: 2.0%>n1≥n2≥0.7%, and n1 is 1.0%-1.6% and n2 is 0.7%-1.3%; (4) The conductive agent in both the first and second positive electrode active slurries is composed of conductive carbon black and carbon nanotubes. The mass percentage of conductive carbon black in the first and second active layers is 0.9%-1.1%, and the mass percentage of carbon nanotubes in the first and second active layers is 0.7%-0.9%. (5) The surface density of both the first and second coatings is 0.2-0.3 (g / 1540.25 mm²), and the ratio of the surface density of the first coating to that of the second coating is m1 / m2, 0.
95. <m1 / m2<1.05; The peel strength of the positive electrode sheet is Y1=a×ln(x1)+ab, where 10≤a≤13, 7≤b≤10, and x1 is the areal density of the binder in the first active layer, x1=m1×n1, with the unit being g / 1540.25 mm². The film resistance of the positive electrode is Y2 = c × e d×c×(x1+x2) Where 0.20≤c≤0.32, 1200≤d≤1800, and x2 is the areal density of the adhesive in the second active layer, x2=m2×n2, with units of g / 1540.25 mm².
2. The preparation method according to claim 1, characterized in that, In step (1), the corona treatment step is as follows: the corona power is 1-6 kW, the corona distance is 2-4 mm, and the corona time is 0.01-120 s; In the drying process, the drying temperature is 40-60 ℃.
3. The preparation method according to claim 1, characterized in that, In step (2), the viscosity of the first positive electrode active slurry and the second positive electrode active slurry are both 5000-15000 mpa.s and the fineness is ≤40 μm.
4. The preparation method according to claim 1, characterized in that, In step (2), the coating speed is 5-30 m / min.
5. The preparation method according to claim 1, characterized in that, In step (3), the drying temperature is 50-150 ℃; after the rolling process, the compaction density of the positive electrode sheet is 2.0-4.5 g / cm³. 3 .
6. A positive electrode sheet prepared by the preparation method according to any one of claims 1-5, characterized in that, The positive electrode includes a current collector, a first active layer disposed on at least one side of the current collector, and a second active layer disposed on the first active layer.
7. The positive electrode sheet according to claim 6, characterized in that, The thickness of the current collector is 5-20 μm; the thickness of the positive electrode is 0.05-2 mm.
8. A lithium-ion battery, characterized in that, It includes the positive electrode sheet as described in claim 6 or 7.
Citation Information
Patent Citations
Pole piece, preparation method thereof and lithium ion battery
CN117080365A
KR20200034382A